Dynamic Simulation of Hanged-type Monorail Vehicle - XIAO Ti; PU Quanwei; CHEN Xihong; TAO Gong (机车电传动)
Structure characteristics of hanged-type monorail vehicle was analyzed, and based on SIMPACK software, criteria of the stability, safety and ride comfort for this type monorail vehicle was discussed. Simulation analysis with different passenger loads in condition of curve and crosswind showed that the lateral displacement of car body and the loads of driving tires and steering tires was an important criteria parameter with limited value. The method to determine a proper pre-pressure for steering tire was discussed and the value of initial press for steering tires for the simulated vehicle was given.